Protocol to study the impact of breast cancer on colonization resistance of mouse microbiota using network node manipulation - Ana Laura Cano-Argüelles; Alejandra Wu-Chuang; Lourdes Mateos-Hernandez; Lianet Abuin-Denis; Apolline Maitre; Janet Avellanet; Arlem García; Dasha Fuentes; Alejandro Cabezas-Cruz (STAR Protocols)
Summary: Network analysis is a powerful tool for investigating complex interactions between different microbial taxa within a community. We present a protocol to study the gut microbial community in a mouse model of breast cancer using a network-based approach. Here, we describe the procedures for tumor cell production and inoculation and 16S rRNA data processing. We then detail steps for constructing co-occurrence networks based on correlations between microbial abundances.For complete details on the use and execution of this protocol, please refer to Wu-Chuang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.